Compositional characterization of complex protopeptide libraries via triboelectric nanogenerator Orbitrap mass spectrometry. (17th July 2019) - Bouza, Marcos; Li, Anyin; Forsythe, Jay G.; Petrov, Anton; Wang, Zhong Lin; Fernández, Facundo M.
Abstract : Rationale: Understanding of the molecular processes that led to the first biomolecules on Earth is one of the key aspects of origins‐of‐life research. Depsipeptides, or polymers with mixed amide and ester backbones, have been proposed as plausible prebiotic precursors for peptide formation. Chemical characterization of depsipeptides in complex prebiotic‐like mixtures should benefit from more efficient ion sources and ultrahigh‐resolution mass spectrometry (UHR‐MS) for elemental composition elucidation. Methods: A sliding freestanding (SF) Triboelectric Nanogenerator (TENG) was coupled to glass nanoelectrospray emitters for the analysis of a depsipeptide library created using 11 amino acids and 3 alpha‐hydroxy acids subjected to environmentally driven polymerization. The TENG nanoelectrospray ionization (nanoESI) source was coupled to an UHR Orbitrap mass spectrometer operated at 1, 000, 000 resolution for detecting depsipeptides and oligoesters in such libraries. Tandem mass spectrometry (MS/MS) experiments were performed on an Orbitrap Q‐Exactive mass spectrometer. Results: Our previous proteomics‐like approach to depsipeptide library characterization showed the enormous complexity of these dynamic combinatorial systems. Here, direct infusion UHR‐MS along with de novo sequencing enabled the identification of 524 sequences corresponding to 320 different depsipeptide compositions. Van Krevelen and mass defect diagrams enabled better visualization of the chemical diversity in these synthetic libraries. Conclusions: TENG nanoESI coupled to UHR‐MS is a powerful method for depsipeptide library characterization in an origins‐of‐life context.